Gender relations, body politics, state power, and religion: Masculinity, male resistance, and reproductive burden - Diana Puspitasari; Yudi Suryadi; Naqiyah Mukhtar (Masyarakat, Kebudayaan dan Politik, 2026)
This study focuses on family planning policies, specifically vasectomy, and the mutuality of partners in reproductive rights rooted in justice (adl), deliberation (tasyawur), and benefit (maslahah). This study draws on perspectives of power relations, gender, and the Quran as a theological source. This study aims to provide a new paradigm for the reciprocal relationship between husbands and wives regarding reproductive rights so that neither party bears the burden alone. The analysis used is critical discourse analysis and contextual theological interpretation. The results depict family planning as a biopower and biopolitical practice fraught with gendered inequality. The low participation and rejection of men in family planning programs demonstrate a strong stigma against reproductive responsibilities within patriarchal and dogmatic frameworks. This indirectly implies an imbalance in the image of the ideal family initially promoted by the government, which is contrary to the Islamic concept of maslahah. This study concluded that the concepts of adl, tasyawur, and maslahah in marriage should encourage open communication that promotes equality within the household, thus making the burden of reproduction a shared responsibility and creating mutual understanding as equal partners (ba’duhum min ba’din).